Not just „general Frost”. The influence of weather factors on the course of Napoleon’s Russian campaign on selected examples - Gralik, Dawid (Armia kontra natura, 2020)
Napoleon’s Russian campaigns one of the best known examples of the impact of weather conditions on the process of military actions. In the article, on selected examples, the influence of weather on the actions and condition of both armies, mainly the Great Army, is analyzed. Adverse weather conditions accompanied the 1812 warfare from the very beginning in the form of a storm that took place at the turn of June and July. Then a period of intense heat began, which caused considerable problems for the soldiers moving in fast marches, who were also deprived of access to drinking water. Finally, the extremely cold winter, even for Russia’s climate, contributed, however not always directly, to deaths of many soldiers on both sides of conflict. Although weather is difficult to see as the main cause of Napoleon’s defeat, it was an extremely important part of 1812 military actions.